2014
DOI: 10.1097/bsd.0b013e318291ce46
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Rigid Upper Cervical Instrumentation in Children

Abstract: Standard 3.5 mm screws can be used for OC and upper cervical instabilities in children aged between 2 and 6 years. Some anchor points appeared safer compared with others. The occipital keel, C1 lateral mass, and C2 laminae offered adequate space for screw placement in almost all cases. C2 pedicles offered adequate space in 49 sides and barely adequate space in 25 pedicles. Transarticular screws could be safely placed in only 4 of 100 sides. Close radiographic assessment of the vertebral artery course and bony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
(21 reference statements)
2
20
1
7
Order By: Relevance
“…27,32 Rigid screw fixation provides superior mechanical stability and improved fusion rates compared with nonrigid techniques. 4,9,10,14,21 Rigid screw fixation often obviates the need for postoperative halo fixation. There are anatomical studies evaluating the feasibility of commercially available screws in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…27,32 Rigid screw fixation provides superior mechanical stability and improved fusion rates compared with nonrigid techniques. 4,9,10,14,21 Rigid screw fixation often obviates the need for postoperative halo fixation. There are anatomical studies evaluating the feasibility of commercially available screws in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…8). While clinical series suggest placement is feasible in most children, recent topographic studies suggest that in younger children there are significant anatomic constraints [6]. The present of anomalous vertebral arteries occur in up to 25% of patients, and although there is some biomechanical strength to unilateral transarticular screws, the rigidity of coupled C1 and C2 screw rod constructs is sufficient [1,17].…”
Section: Transarticular Screwsmentioning
confidence: 99%
“…Ultimately, almost all pediatric patients will have anatomy that will allow for placement of screws into C2. Geck, in his study of morphology in pediatric patients, showed that the vast majority of children were able to accept intralaminar screws even as young as 2 years of age [6]. There was more variability in the pedicle size in the patient population suggesting that intralaminar screws in young children remain a reasonable first option for screw placement.…”
Section: C2 Screw Fixationmentioning
confidence: 99%
See 2 more Smart Citations